Surogacy – challenge to the legislation of the Republic of Bulgaria - Peneva, Lidiya (Law Journal of New Bulgarian University, 2021)
Surrogate motherhood is a modern socio-economic phenomenon that needs legal regulation in the Republic of Bulgaria. This article presents the generally accepted view of it and the differentiated types of surrogacy. With the comparative method, the legislative approach to it was analysed in the countries of the European legal family and beyond. Finally, is presented position in the Republic of Bulgaria.